2010
DOI: 10.1089/acm.2009.0445
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial of St. John's Wort for Smoking Cessation

Abstract: Introduction: St. John's wort (SJW) is a widely used herbal supplement. The predominant mechanism(s) accounting for the activity of SJW in vivo are, however, unclear. The purpose of this study was to investigate the efficacy of SJW for smoking cessation. Methods: We conducted a randomized, blinded, placebo-controlled, three-arm, dose-ranging clinical trial. A total of 118 subjects were randomly allocated to receive SJW 300 mg, 600 mg, or a matching placebo tablet 3 times a day combined with a behavioral interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 24 publications
(26 reference statements)
3
17
0
Order By: Relevance
“…The small sample size and relatively high proportion of treatment noncompleters limit our interpretation of the results; however, it is notable that our experiences with the proportion of individuals telephone screened who enrolled in studies, as well as the percent of treatment non-completers, are consistent with those of other recent studies of treatments for cannabis dependence and nicotine dependence. [29][30][31][32][33] Other limitations of this study included duration of follow-up and heterogeneity of the sample with respect to baseline cigarette smoking. Previous studies utilizing CBT for substance use disorders suggest that the benefits of CBT may emerge months after treatment ends.…”
Section: Discussionmentioning
confidence: 99%
“…The small sample size and relatively high proportion of treatment noncompleters limit our interpretation of the results; however, it is notable that our experiences with the proportion of individuals telephone screened who enrolled in studies, as well as the percent of treatment non-completers, are consistent with those of other recent studies of treatments for cannabis dependence and nicotine dependence. [29][30][31][32][33] Other limitations of this study included duration of follow-up and heterogeneity of the sample with respect to baseline cigarette smoking. Previous studies utilizing CBT for substance use disorders suggest that the benefits of CBT may emerge months after treatment ends.…”
Section: Discussionmentioning
confidence: 99%
“…One randomized, blinded, placebo-controlled trial of 118 smokers found that St. John's Wort did not promote smoking abstinence or attenuate withdrawal symptoms (Sood et al, 2010). These results indicate that St. John's Wort is not indicated for smoking cessation.…”
Section: Herbal and Dietary Supplementsmentioning
confidence: 98%
“…Two small trials of St John's wort have failed to detect a significant effect on quit rates or withdrawal symptoms [330,331]; although there may be some worthwhile benefits for preventing weight gain [330]. One trial of SAMe did not find significantly increased tobacco abstinence rates nor decreased nicotine withdrawal symptoms compared to placebo [332], and evidence is lacking for a dose response [86].…”
Section: Relative Efficacymentioning
confidence: 99%
“…St John's Wort is not associated with adverse events, but is contraindicated for concurrent contraceptive use, and has mild side-effects including anxiety, dizziness, abdominal bloating and dry mouth [331,334].…”
Section: Relative Safetymentioning
confidence: 99%
See 1 more Smart Citation